Fundraising matters: communication skills training for non-clinical hospice staff. Issue 2 (1st September 2011) - Russell, Sarah; Jo, Fernandes; Doughty, Jess
Abstract : Introduction: Communication skills training is traditionally directed towards clinicians. At St Francis we identified a need to support our fundraising staff in their confidence in their daily conversations. These conversations often included distressed bereaved relatives. Aims: To increase the communication skills and confidence of fundraising staff in the community and public setting. Methods: A ½ day interactive workshop using videoed role play with a Connected actor, facilitator and communication skills trainer. The role play was based upon scenarios provided by the fundraisers prior to the workshop. They completed a pre and post workshop confidence questionnaire and a follow-up one 3 months later. Results: 11 fundraising staff attended. Scenarios revolved around distressed relatives (expected and unexpected), and questions about care and dying in the context of fundraising for the hospice. Pre and post course questionnaires showed an increase in confidence in challenging conversations. The workshop was highly evaluated. Discussion: ▶ Fundraising staff do not necessarily have the day to day experience of clinical conversations to draw upon, but bereaved families have the same expectations of them as clinical staff in terms of conveying empathy and compassion. ▶ There is a parallel agenda of empathy versus receiving a donation, eliciting a "story" or discussing a fundraising event. ▶ The communication challenges are similar to clinicians and the power of silence is a similar take home message. ▶ The advantages of using videoed role play include giving participants the chance to see and discuss things they might have missed first time around. Conclusion: Fundraising staff have similar communication training motivation as clinical staff. The workshop was a worthwhile education event, albeit seeming too short – in the future it would be beneficial to mix more non-clinical staff to give a wider breadth of discussion and experience – this is planned for later in 2011.